CARLONI, Karla. Forças armadas e democracia no Brasil – o 11 de novembro de 1955. Rio de Janeiro: Editora Garamond, 2012 (172 p.) - REA Editor (Revista Espaço Acadêmico, 2012)
CARLONI, Karla. Forças armadas e democracia no Brasil – o 11 de novembro de 1955. Rio de Janeiro: Editora Garamond, 2012 (172 p.)